Uji Efektivitas Nefroprotektif Ekstrak Buah Kopi (Coffea Arabica L) Terhadap Perubahan Morfologi Ginjal dan Tumor Necrosis Factor-Alpha (TNF- α) pada Tikus yang Diinduksi Gentamisin - Maria Ulfah Siregar; Asyrun Alkhari Lubis; Hariyadi Dharmawan Syahputra (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Gentamicin is a nephrotoxic antibiotic that induces kidney damage through oxidative stress and elevated TNF-α levels. Coffee fruit (Coffea arabica L.) contains bioactive compounds such as polyphenols and chlorogenic acid with potential nephroprotective effects. Objective: This study aimed to evaluate the nephroprotective efficacy of coffee fruit extract on renal morphological changes and TNF-α levels in gentamicin-induced rats. Methods: An experimental randomized group design was employed using 30 male Wistar rats divided into five groups: normal control, negative control (gentamicin 100 mg/kgBW), and three treatment groups receiving gentamicin plus coffee fruit extract at doses of 100, 200, and 400 mg/kgBW. Parameters assessed included renal histopathological changes (HE staining) and serum TNF-α levels (ELISA). Results: Administration of coffee fruit extract significantly improved renal tubular morphology and reduced TNF-α levels compared to the negative control group (p<0.05). The most protective effect was observed at a dose of 200 mg/kgBW. Conclusion: Coffee fruit extract exhibits nephroprotective activity against gentamicin-induced kidney injury, as evidenced by improved histological structure and reduced TNF-α levels, suggesting its potential as a natural agent for preventing nephrotoxicity.